Intelijen Bisnis dan Pengambilan Keputusan, dan Strategi Bisnis Industri Perbankan di Indonesia: Studi Bank Indonesia - Sari, Nur Malita; Adha , Suhroji (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
This research tries to explore the role of BI as internal business intelligence in improving decision making, increasing operational efficiency and effectiveness, increasing competitiveness, improving risk management, and increasing customer satisfaction. The research method used is qualitative, with a case study approach. Data was collected through in-depth interviews with key informants at various levels of the organization. The research results show that BI plays an important role in supporting decision making and business strategy. BI helps organizations to collect, analyze and understand data from various internal and external sources. This understanding can then be used to make more informed and strategic decisions. The findings of this research provide an important contribution to the understanding of the role of BI in organizations. This research also provides practical implications for managers who want to use BI to improve their decision making and business strategy